Old age is Both a Calm sea and a Restless Port: An Instrument for Examining Beliefs About the old age, Elderly and Elderly Education - Mišović, Jana; Gojak, Natalija; Milošević, Zorica (Zbornik Instituta za kriminološka i sociološka istraživanja, 2022)
Scientific and socio-political interest in old age and the elderly is stimulated by the global trend of demographic ageing of the population. There are many different social narratives available about the old age as a period of life, the elderly as a social category and the education intended for them, and all these narratives can be grouped into three approaches to the theory, practice and policy of elderly education: the concept of disengagement, the concept of expansive engagement and the concept of constructive and competent engagement. An instrument for examination of beliefs about old age, the elderly and elderly education was created, which is based on the theoretical premises of the aforementioned approaches. In order to examine the reliability of the created instrument, a pilot study was conducted on a sample of 40 andragogy students at the Faculty of Philosophy, University of Belgrade. The paper presents the results of a pilot study of the beliefs of andragogy students about old age, elderly and elderly education, as well as the metric characteristics of the reliability of the created instrument. The instrument was revised based on the obtained research results and is presented at the end of the paper.